Zero-Waste-Based Design and Operational System Planning of 3R Waste Facilities for Green Campus: Perencanaan Desain dan Sistem Operasional Fasilitas Pengolahan Sampah 3R Berbasis Zero Waste untuk Green Campus - Dwi Vanesha Salsabilah; Praditya Sigit Ardisty Sitogasa (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2026)
Domestic and academic activities at UPN “Veteran” Jawa Timur generate significant amounts of solid waste, while the existing management system still applies a conventional linear approach (collect–transport–dispose). This study aims to identify existing conditions, analyze waste characteristics, and formulate a technical design for a Zero Waste-based TPS 3R facility. Sampling results showed that waste generation reached 943.641 kg/day (11.525 m³/day), dominated by food waste (26.52%) and garden waste (12.43%), followed by cardboard (8.57%), PP/Polypropylene plastic (7.63%), and LDPE/Low Density Polyetylene plastic (7.34%). The absence of source segregation causes mixed waste to enter the facility, resulting in low recovery rates and high dependence on landfill disposal. To improve management efficiency, a TPS (Tempat Penampungan Sementara) 3R (Reduce, Reuse, Recycle) operational scenario was developed by directing organic waste to Black Soldier Fly (BSF) bioconversion and In-Vessel Composting, recyclable inorganic materials to the recycling industry, non-recyclable plastics to Refuse Derived Fuel (RDF) and pyrolysis processes, and hazardous waste (B3) to licensed operators. This integrated management system reduces final landfill residue and achieves a waste reduction target of 72,81%. The facility is designed with a one-way operational flow consisting of receiving and sorting areas, processing units, product storage, leachate treatment, residue storage, offices, parking areas, and sanitation facilities.